Peru : Selected Issues Paper. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
The purpose of the study is to examine Peru's effective interest spread through accounting decompositions, financial ratio analysis, and spread regressions. The government's financial restructuring programs accelerated the banking sector consolidation process. Robustness of Peru's credit system and interest rate decomposition has also been viewed. Three key financial ratios-return on equity (RoE), return on assets (RoA), and net interest margin (NIM)-focused by financial statements, have also been studied. Finally, the framework of Espino and Carrera used for the estimation of interest rate spreads has also been discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet